1999
DOI: 10.1007/s004210050580
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of electrical activity in the triceps surae at maximum isometric contraction with the knee and ankle at various angles

Abstract: The purpose of this study was to test the endurance of the soleus muscle, and to examine the joint position at which it is most active, while simultaneously suppressing the activity of the gastrocnemius. Ten young males performed maximum isometric contraction of the triceps surae for 100 s, and the endurance and plantar flexion torque of this muscle were measured at various angles of the knee and ankle joints. The electromyogram was measured simultaneously and subsequently converted into integrated electromyog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 17 publications
6
25
0
3
Order By: Relevance
“…5). This agrees with the earlier reports which examined the EMGs of MG under static (Cresswell et al, 1995;Miaki et al, 1999) and concentric (Carpentier et al, 1996(Carpentier et al, , 1999Price et al, 2003) conditions. In the case of surface EMG, the decrease in the MG EMG with knee flexion may be due to the impaired neuromuscular transmission or changes in electrode-muscle configuration (Cresswell et al, 1995).…”
Section: Article In Presssupporting
confidence: 94%
“…5). This agrees with the earlier reports which examined the EMGs of MG under static (Cresswell et al, 1995;Miaki et al, 1999) and concentric (Carpentier et al, 1996(Carpentier et al, , 1999Price et al, 2003) conditions. In the case of surface EMG, the decrease in the MG EMG with knee flexion may be due to the impaired neuromuscular transmission or changes in electrode-muscle configuration (Cresswell et al, 1995).…”
Section: Article In Presssupporting
confidence: 94%
“…The maximal isometric torque measurements obtained in this study were similar to those previously published for the flexor and extensor muscles of the knee and ankle joint, with comparable joint positioning. 9,11,13,23,24,28,29,36 In some instances, authors reported the maximal isometric force or torque after only two contractions. 29,37 For accurate assessment of maximal strength, our results indicate that patients should perform five MVCs to ensure that the largest maximal torque is recorded.…”
Section: Discussionmentioning
confidence: 98%
“…As the CPN branches into the deep peroneal nerve that innervates dorsiflexor muscles such as TA, and the superficial peroneal nerve, that innervates the plantar flexor muscles PL and PB (Benzon et al 1997), the anaesthetic block of the CPN not only abolished activation of TA, but also removed activation of the synergist plantar flexors, PL and PB. The contribution of all muscles, other than the triceps surae, to plantar flexion torque is estimated to range between 15% and 38% (Arndt et al 1998;Gregor et al 1991;Miaki et al 1999;Murray et al 1976). Therefore, anaesthetic block of the CPN may account for a large proportion of the reduction in post-block torque by abolishing activation of the plantar flexor muscles, PL and PB.…”
Section: Discussionmentioning
confidence: 99%